Active Debate to Enhanced Students’ Speaking Activity - Muktamir Muktamir (Universitas PGRI Semarang, 2020)
Debate is supposed to be an excelent model of an analytical and communicative process that students learned. In this activity , students have much more opportunities to explore their speaking ability and to share argument critilly and cooperatively. The aim of the research was to describe the application of English debate to enhanced student’s speaking ability. The research design was classroom action research conducted in two cycles with two meeeting each. Each cycles consisted of planning , implementation, observation, and reflection. While for data collection, the research used some intruments i.e observation both in preliminary study and in the action , journal , questionnaire and handy cam. The finding showed that after cycle II was implemented, there were 25 from 34 students who actively participated in the speaking activity , and the average score of the students speaking ability could reach 9 the students questionnaires about the english debate showed that the students felt more confident to speak after the implementation of english debate, and even debate could be very satisfying and entertaining.